Sulfur doping of M/In2O3 (M=Al,W) nanowires with room temperature near infra red emission - M. Zervos; C. Mihailescu; J. Giapintzakis; A. Othonos; A. Travlos (AIP Advances, 2015)
We have investigated the growth of Al doped In2O3 nanowires via the vapor-liquid-solid mechanism at 800°C using Au as a catalyst. We find that the Al is not incorporated into the cubic bixbyite crystal structure of In2O3 but nevertheless was detected in the form of Al2O3. The nanowires had metallic like conductivities and exhibited photoluminescence at 2.3 eV which shifted to 1.5 eV after exposure to H2S above 500°C due to the formation of β-In2S3 and deep donor to acceptor transitions with a lifetime of ≈1 μs. The near infra red emission was also observed in W/In2O3 but not in W/SnO2 core-shell nanowires after processing under H2S at 600°C, confirming it is related to β-In2S3. The nanowires remain one dimensional up to 900°C due to the shell which is interesting for the fabrication of high temperature nanowire sensors.